THE EFFECT OF BRAND IMAGE, PRODUCT QUALITY AND PRICE ON CONSUMER SATISFACTION IN IMPLORA PRODUCTS - Suwardi Suwardi; Alawiyah Prawita Salsabila (Asosiasi Dosen Muda Indonesia, 2023)
Facial care is an obligation that cannot be abandoned by anyone, especially young people (adolescents). The purpose of this study was to analyze the effect of brand image, product quality, and price on consumer satisfaction with Implora products. The method of analysis in this study used quantitative primary data, the test stages carried out were: validity test, reliability test, normality test, linearity test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, t test, F test and coefficient of determination. The data used in this study used a questionnaire instrument, and valid data were collected by 100 respondents. The sampling method in this study was non-probability sampling with accidental sampling technique. the testing tool used was SPPS 25. The results showed that the brand image variable did not have a significant effect on customer satisfaction while the product quality and price variables had a significant effect on customer satisfaction and there was a simultaneous effect of brand image, product quality, and price on customer satisfaction. as well as the most dominant variable on consumer satisfaction is the product quality variable.